Recent Advances in Drug Delivery Strategies for High-Risk BCG-Unresponsive Non-Muscle Invasive Bladder Cancer: A Brief Review from 2018 to 2024 - Feng Qu; Saloni Darji; David H. Thompson (MDPI AG, 2024)
High-risk BCG-unresponsive non-muscle invasive bladder cancer (NMIBC) is a condition that is typically treated with Bacillus Calmette-Guérin (BCG) therapy. Unfortunately, NMIBC is characterized by high recurrence, with a significant percentage of BCG patients ultimately requiring radical cystectomy. As a consequence, the development of effective new therapies to avoid RC has become a rapidly evolving field to address this unmet clinical need. To date, three biologics-Keytruda, Adstiladrin, and Anktiva-have been approved by the FDA, and multiple drug modalities, particularly gene therapies, have shown promising results in clinical trials. Advances in drug delivery strategies, such as targeted delivery, sustained release, and permeabilization of protective layers, are critical in overcoming the challenges posed by therapeutic intervention in bladder cancer. This review focuses on high-risk BCG-unresponsive NMIBC therapies that have been or are currently being investigated in clinical trials, offering a broad overview of the delivery system designs and up-to-date clinical outcomes that have been reported as of July 2024. It aims to inform the development of future drug delivery systems for second-line therapies in high-risk BCG-unresponsive NMIBC.